Polymer materials derived from the SEAr reaction for gas separation applications. (13th February 2023) - Matesanz-Niño, Laura; Esteban, Noelia; Webb, Matthew T.; Martínez-Gómez, Aránzazu; Suárez-García, Fabián; González-Ortega, Alfonso; Miguel, Jesús A.; Palacio, Laura; Galizia, Michele; Álvarez, Cristina; Lozano, Ángel E.
Abstract: A set of linear polymers were synthesized utilizing an electrophilic aromatic substitution reaction (SEAr) between biphenyl and ketone containing electron-withdrawing groups (isatin, IS; N-methylisatin, MeIS; and 4, 5-diazafluoren-9-one, DF). Optimization of the polycondensation reaction was made to obtain high molecular weight products when using DF, which has not previously been used for linear polymer synthesis. Due to the absence of chemically labile units, these polymers exhibited excellent chemical and thermal stability. Linear SEAr polymers were blended with porous polymer networks derived from IS and MeIS, and both neat/mixed materials were tested as membranes for gas separation. The gas separation properties of both pristine polymers and mixed matrix membranes were good, showing some polymer membrane CO2 permeability values higher than 200 barrer. Graphical abstract: Image 1 Highlights: Linear polymers derived from biphenyl and activated ketones were obtained. Microporous polymer networks (POPs) derived from activated ketones and trifunctional aromatic groups were prepared. Mixed matrix membranes (MMMs) showed good mechanical properties. Linear polymers and MMMs exhibited excellent chemical and thermal stability. The gas separation productivity of MMMs was better than that of neat polymers.